Propriedades químicas, físicas e biológicas de um sistema agrícola sob rotação de culturas. - Rosa, Danielle Medina (2013)
Crop rotation is a basic action to ensure the viability of no-tillage system; however, it is less accepted and practiced by farmers. Thus, this study aims to verify effects of establishing a crop rotation scheme on chemical and physical properties of soil, on biological and agronomics characteristics of crops and as suppressive effect on the weed community. So, under the no-tillage system, in 2010, the cover crops of dwarf mucuna (Mucuna deeringiana), dwarf pigeon pea (Cajanus cajan) and sun hemp (Crotalaria juncea), and corn crops were implemented; in 2011, the cover crops of canola (Brassica napus), crambe (Crambe abyssinica) and turnip forage (Raphanus sativus), and soybean crops were implemented. The physical and chemical properties were determined prior to deployment, after management of cover crops and its harvesting. Changes in the soil were monitored by the determination of organic matter, bulk density, macroporosity, microporosity, total porosity and water content. The quality of cover crops was determined by the characteristics of straw, as dry mass and C/N ratio. The population of weeds was determined after 30 days the cover crops sowing and 30 to 60 days due to the crops development. The assessment was performed with the introduction of random frame, hurled four times by portions. The seedling emergence was determined during the crop harvest. In addition, chlorophyll content and leaf analyses were determined. In the laboratory, after harvesting, it was determined the yield and seeds quality. The experimental design was completely randomized, with four treatments in each experimental year (three cover crops plus one control), with five replicates per treatment, totalizing 20 portions. Results obtained were submitted to ANOVA and means comparison was conducted by the Scott-Knott test at 5% of probability, using the SISVAR software. Some variables were correlated. In the agricultural year 2010/2011, improvements were observed in the physical and chemical soil properties after the management of these plants. There was increase in leaf nitrogen content of maize in treatments with cover crops; and the yield and seed quality were not affected. In agricultural year 2011/2012, there was increase in the carbon soil content, however, canola was affected by climatic conditions and crambe influenced negatively soybean. In the two agricultural years, the weeds were controlled by cover crops, which presented adequate soil cover. In general, there was increase in the organic matter content of soil, and the chemical and physical properties presented no consistent changes. Thus, we highlight the necessity of crop rotation systems validated in a regionalized way, according to the different soil and climatic conditions of the State of Paraná.